Categorization of Product Innovations in the Residential Condominium Projects - Pawanacharurn, Vitoon; Tochaiwat, Kongkoon; Janjamlha, Tipsuda (International Journal of Building, Urban, Interior and Landscape Technology, 2021)
Product innovation in residential projects is a key component that real estate developers use as a key selling point today. However, product innovation is used in a variety of project elements. An analysis to categorize product innovations based on the degree of influence in the purchasing decisions of project residents can help them understand and choose innovations in order to effectively add value to their projects. This research aimed to study the key categories of the innovative products in residential condominiums of residents in Bangkok, Thailand, from surveying 300 condominium buyers and performing Exploratory Factor Analysis by Principal Component Analysis method, rotating perpendicular component axis by Varimax method. The results showed that the set of variables were analyzed in 5 groups which in order of the influence of the group of innovation elements affecting the decision to buy condominiums from greatest to least is as follows: (1) Digital innovation and intelligent systems, (2) Health and safety innovation, (3) Energy innovation, (4) Construction innovation, and (5) Automotive application innovation, which can explain the cumulative variance of 74.22%. The results of the research showed the degrees of influence on the purchasing decisions of various product innovations, which can provide competitive advantages for property developers.